The agglomeration state of nanoparticles can influence the mechanism of their cellular internalisation - Halamoda-Kenzaoui, Blanka (J Nanobiotechnology, 2017)
BACKGROUND: Significant progress of nanotechnology, including in particular biomedical and pharmaceutical applications, has resulted in a high number of studies describing the biological effects of nanomaterials. Moreover, a determination of so-called “critical quality attributes”, that is specific physicochemical properties of nanomaterials triggering the observed biological response, has been recognised as crucial for the evaluation and design of novel safe and efficacious therapeutics. In the context of in vitro studies, a thorough physicochemical characterisation of nanoparticles (NPs), also in the biological medium, is necessary to allow a correlation with a cellular response. Following this concept, we examined whether the main and frequently reported characteristics of NPs such as size and the agglomeration state can influence the level and the mechanism of NP cellular internalization. RESULTS: We employed fluorescently-labelled 30 and 80 nm silicon dioxide NPs, both in agglomerated and non-agglomerated form. Using flow cytometry, transmission electron microscopy, the inhibitors of endocytosis and gene silencing we determined the most probable routes of cellular uptake for each form of tested silica NPs. We observed differences in cellular uptake depending on the size and the agglomeration state of NPs. Caveolae-mediated endocytosis was implicated particularly in the internalisation of well dispersed silica NPs but with an increase of the agglomeration state of NPs a combination of endocytic pathways with a predominant role of macropinocytosis was noted. CONCLUSIONS: We demonstrated that the agglomeration state of NPs is an important factor influencing the level of cell uptake and the mechanism of endocytosis of silica NPs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12951-017-0281-6) contains supplementary material, which is available to authorized users.